Pemberdayaan Masyarakat Desa Pasir Emas Pada Bidang Kesehatan Dan Literasi Digital - Gora Markus Fajar Hutahaean; Feliks Gamaliel Barus; Indri Wulandari; Yolanda Yolanda; Tya Ariani; Nabela Okta Viani; Natasya Prithadya; Mutia Fitri Annisa (Universitas Kristen Indonesia Toraja, 2023)
This article discusses empowering the Pasir Emas Village Community in the fields of health and digital literacy. The aim of this activity is to provide valuable learning experiences to students through direct involvement in society to discover, formulate, study and recognize the potential of society and find solutions to problems rationally by fostering motivation to utilize their own potential and the second aim is to provide opportunities for students. to develop thinking based on science. This KKN activity will start with debriefing, carrying out activities, preparing reports and evaluating. KKN starts on July 10 2023 to August 18 2023 in Pasir Emas Village, Kuantan Singingi Regency, Singingi District. We, the Unri Kukerta team, focus more on community empowerment. Our work programs are Disaster Mitigation Socialization, Waste Recycling and Making Ecobrics, Making Waste Decomposition Plags, Educating Gender Equality for Teenagers, Making Water Filter Tools, Strengthening Pre-School Age Children's Literacy Using Used Used Materials, Qris Socialization, Making Alternatives or adding other variations of dodol products, MSMEs sharing with local entrepreneurs regarding integrated marketing communication and public speaking in community business development such as in tofu and tempeh factories and helping organize correspondence filing in Pasir Emas Village. In general, the activities or work programs that we carry out can run well and smoothly.